Foundations of interior design - Slotkis, Susan J. (Fairchild Books, Bloomsbury, 2017)
"The third edition of Foundations of Interior Design, 3rd edition, offers a thorough update to this introduction to the creative, technical and business aspects of the interior design profession. By surveying design history, the elements and principles of design, professional practice, and more, Susan Slotkis provides a practical and comprehensive overview. This new edition includes more coverage of sustainability and a thorough update of lighting topics. Online resources, including a timeline, multiple choice quizzes, flashcards, and other study tools, supplement the book"--Resumé vydavatele
Terminologický slovník
Keywords: interiéry; dekorace interiérů; vybavení interiérů; interiors; interior decoration; interior equipment; příručky; handbooks and manuals